A92: Intensive Physical Therapy With Desensitization in Collaboration with Psychological Care Is a Successful Outpatient Treatment for Amplified Musculoskeletal Pain Syndrome. Issue 11 (March 2014) - Rahimi, Homaira; Siegel, David M.
Abstract : Background/Purpose: Amplified musculoskeletal pain (AMP) syndrome is a debilitating clinical entity primarily affecting adolescent girls in which severe pain and tactile sensitivity (allodynia) are present in a particular body region sometimes with associated signs of pallor, cutaneous hypothermia and atrophy, or pain is in a generalized distribution (fibromyalgia syndrome). Treatment focusing on desensitization, physical reconditioning, and psychological intervention has been suggested as effective therapy. We present our early experience in a protocolized, outpatient AMP program. Methods: Patients seen at the Pediatric Rheumatology group and diagnosed with AMP were referred to the Golisano Children's Hospital Amplified Musculoskeletal Pain Program (GCHAMPP) for evaluation and enrollment in the 8 week outpatient program. There was no restriction on co‐morbidities, except conditions preventing ability to participate in intensive physical therapy (PT) and occupational desensitization therapy (OT). Evaluation included assessing muscle strength, endurance, and coordination, as well as psychological screening. The number of PT/OT sessions were individualized (mean = 16, range = 6–28). Results: Of 30 patients enrolled in the program, 93% were female, 90% were Caucasian, and mean age was 14.8 years (range 10–19). 57% successfully completed the full program. All had a return to normal function and 41% had resolution of pain. 35% had initiated psychotherapy/counseling along with PT/OT. Reasons for not completing the program included needing to address other medical conditions (23%) or unknown (46%). Notably, the majority of those who withdrew had not initiated psychotherapy along with PT/OT (69%). More than a quarter of patients could not complete therapy due to insurance non‐payment (31%). Conclusion: Our initial experience with a cohort of pediatric patients with AMP validates prior studies showing intensive physical therapy with desensitization is a successful treatment. More than half of our patients completed the program, with all having return to normal function and almost half having resolution of pain. Furthermore, we noted that more than two‐thirds of patients who chose to withdraw had not initiated psychotherapy along with PT/OT, suggesting that psychotherapy may allow patients to complete the physical demands of treatment. The other contribution of psychotherapy, and perhaps the more potent influence, is that while the PT/OT is proceeding, psychotherapy is uncovering and addressing the individual and family psychodynamics that are part of the process underlying the onset and perpetuation of symptoms. Notably, one quarter of patients did not complete the program due to failure of insurance carriers to recognize intensive PT/OT as a known treatment for AMP and distinct from the standard PT/OT sessions for other rheumatic or orthopedic conditions. Our findings support the use of intensive therapy and desensitization along with family oriented psychological intervention to treat AMP in a select population of children with pain. Further clinical trials with larger cohorts are necessary to validate these findings.